Neisseria meningitidis RTX Protein FrpC Induces High Levels of Serum Antibodies during Invasive Disease: Polymorphism of frpC Alleles and Purification of Recombinant FrpC - Osička, Radim (American Society for Microbiology, 2001)
The Neisseria meningitidis FAM20 strain secretes two proteins of unknown function, FrpA and FrpC, which contain typical RTX domains found in cytotoxins from other gram-negative pathogens. To evaluate whether the Frp proteins could be involved in meningococcal virulence, 65 isolates of all serogroups were screened by PCR for the presence of both frp genes. The frpA allele was, however, poorly conserved. A single strain harbored an frpA allele of the previously described size, while large insertions were detected in the frpA loci of 22 isolates (34%), and the 42 remaining isolates (65%) did not contain frpA at all. In contrast, frpC alleles, albeit of variable length, were detected in all invasive and most carrier strains. This suggests that meningococci may produce a family of FrpC proteins of various molecular masses. High levels of both immunoglobulin G (IgG) and IgA class antibodies recognizing recombinant FrpC were indeed detected in convalescent-phase sera of most patients at 2 and 4 to 5 weeks after the first symptoms of meningococcal disease. These results show that FrpC-like proteins are produced and may play a role in invasive meningococcal infections.